Strategic Management And Organizational Performance: : A Case Of Lyamujungu Sacco, Kabale District, Uganda - Agaba, Agaba Moses; Turtasingura John Bosco; Kabagambe Jesse David (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The study was set to establish the effect of strategic management on organizational performance a case of Lyamujungu SACCO. The study employed a correctional sectional research design. It involved quantitative and qualitative methods which enabled the study to evaluate the relationship between the study variables. A sample of 105 respondents were selected using simple random sampling and purposive sampling techniques. The quantitative and qualitative data from the respondents was analyzed using SPSS Version 21.0 and thematic analysis respectively. Quantitative results in form of descriptive statistics, correlations and regressions were presented in tables based on the study objectives. The study found out that strategy management, has a positive significant relationship with organizational performance of SACCOs (r = .962, P≤.01). With these findings, the study makes a contribution of providing empirical evidence that has been widely absent to channel the presently zealous discussion surrounding issues of strategic management and organizational performance in Lyamujungu SACCO. The study recommends that, for effective strategic management at Lyamujungu SACCO management should work hand with Board members and all other stakeholders implement the resolutions of the Annual general meeting as well the Board meeting.